Karolinska Institutet 200-Year Anniversary Symposium on Injuries to the Spinal Cord and Peripheral Nervous System - An Update on Recent Advances in Regenerative Neuroscience - Mattias K. Skold (Frontiers Research Topics, 2017)
The present E-book consists of original articles and reviews published in our Research Topic on injuries to the spinal cord and peripheral nerves and presents a wide array of novel findings and in depth discussions on topics within the field of nerve injury and repair. Our aim with this Research Topic is to bring together knowledge spanning from basic laboratory studies to clinical findings and strategies within the field of spinal cord and nerve injury and repair. We hope this publication will provide a basis for accelerated knowledge exchange within the field and hopefully a subsequent increase in research efforts and collaborations.